EFFECTS OF FAMILY SMOKING HABITS ON BRONCHOPNEUMONIA INCIDENCE AMONG TODDLERS - Muhammad Iqbal S; Cut Oktaviyana; Darman Ajali (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Bronchopneumonia, one of the variants of pneumonia that commonly affects the bronchi and alveoli, especially in toddlers, is often caused by exposure to cigarette smoke in the surrounding environment. In 2019, there were 2,157 cases of bronchopneumonia in toddlers in Aceh Province. The presence of family members who smoke increases the risk of bronchopneumonia in toddlers because cigarette smoke can disrupt lung defense mechanisms. This research aims to determine the influence of family members' smoking behavior on the incidence of bronchopneumonia in toddlers in the pediatric ward of RSUD dr. H. Yuliddin Away Tapaktuan, South Aceh.Methods: This research design is quantitative with a cross-sectional study approach. The study population consisted of 71 toddlers, with 41 respondents selected as samples using purposive sampling technique. The study was conducted from February 7 to 15, 2024, using interview instruments and examination sheets to assess bronchopneumonia criteria. Data analysis was performed using the chi-square test.Results: The research findings indicate that the average family members of toddlers who smoked the most were the toddlers' parents, with a percentage of 56%, and smoking habits indoors reached 68.3%, while the proximity of smokers to toddlers reached 90.2%. The chi-square test analysis showed the influence of family members' smoking behavior on the incidence of bronchopneumonia in toddlers, with a p-value of 0.007 (< α = 0.05).Conclusion: The smoking behavior of family members can cause respiratory disorders in toddlers and thus increasing the risk of bronchopneumonia